Anlysis Of Effect Website STIKOM Institutional Repositories (SIR) At Institute Of Business And Information STIKOM Surabaya - Muchammad, Rizqy; Sulistiowati, Sulis; Churniawan, Agus Dwi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
STIKOM library has four online services such as web one sir.stikom.edu, sir.stikom.edu is institutional repository that contains information collection of scientific papers related to the work of the academic society that is open to anyone. Nevertheless website sir.stikom.edu now deemed less attractive academic faculty and students STIKOM, even based on the results of interviews with the library manager that the academic faculty and students STIKOM more like its old access online services web digilib.stikom.edu. Based on these problems, then this final project conducted a preliminary study to measure the quality of a website in terms of end-user satisfaction and site visitors using WebQual, Of the deployment of questionnaires conducted obtained a sample of 90 respondents. Data from the questionnaire testing the variables with the validity and reliability. Furthermore, the normality test data and test assumptions as a condition for the implementation of the next step that multiple linear regression. Â Based on the results of this test showed that the variable quality of use (usability) with a coefficient of 0.266, the quality of information (information quality) of 0.141, and the quality of interaction (interaction quality) amounted to 0.196 positive and significant impact on customer satisfaction (customer satisfaction) with a coefficient of determination amounting to 0.611 which means WebQual contribution to customer satisfaction by 61%.